2021
DOI: 10.48550/arxiv.2112.06374
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Learning Generalizable Vision-Tactile Robotic Grasping Strategy for Deformable Objects via Transformer

Abstract: Reliable robotic grasping, especially with deformable objects such as fruits, remains a challenging task due to underactuated contact interactions with a gripper, unknown object dynamics and geometries. In this study, we propose a Transformer-based robotic grasping framework for rigid grippers that leverage tactile and visual information for safe object grasping. Specifically, the Transformer models learn physical feature embeddings with sensor feedback through performing two pre-defined explorative actions (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Similarly, Low [27] used you only look once, version 3 (YOLOv3) for object detection and successfully switched between three gripper poses based on detection results. Other networks, including convolutional neural network (CNN) [183] and Transformer, [184] have also provided reliable solutions for object detection, thus enhancing grasping capabilities. The performance of sensors in the aforementioned four categories is documented in Table 7-10, along with their respective strengths and limitations.…”
Section: Imaging Sensorsmentioning
confidence: 99%
“…Similarly, Low [27] used you only look once, version 3 (YOLOv3) for object detection and successfully switched between three gripper poses based on detection results. Other networks, including convolutional neural network (CNN) [183] and Transformer, [184] have also provided reliable solutions for object detection, thus enhancing grasping capabilities. The performance of sensors in the aforementioned four categories is documented in Table 7-10, along with their respective strengths and limitations.…”
Section: Imaging Sensorsmentioning
confidence: 99%
“…Yi et al [22] extracted tactile features from signals and proposed a new genetic algorithm-based integrated hybrid sparse limit learning machine for grasp stability recognition tasks. Han et al [23] introduced a Transformer-based robotic grasping framework for rigid gripper robots, leveraging tactile and visual information to ensure secure object grasping. Evaluation on slip detection and fruit grasping datasets demonstrated that Transformer models exhibit higher grasping accuracy and computational efficiency compared to traditional CNN + LSTM models.…”
Section: Target Grasping Status Detectionmentioning
confidence: 99%